Preliminary study: Predictors for success in an important premedical subject at a South African medical school - Nicolaas Allers; Leon Hay; Runette Janse van Rensburg (South African Medical Association, 2016)
Background. Admission to Sefako Makgatho Health Sciences University, Pretoria, South Africa is determined by the student’s Matriculation (Matric) results, while the writing of the National Benchmark Test (NBT) is not compulsory. An average student pass rate of 80.1% in physiology (MB ChB II) in the past 13 years compelled this institution to investigate which criteria in the selection process could be predictors for success in physiology, a fundamental discipline for medical studies. Objectives. To compile a profile of very successful physiology students and those who failed the subject, and to identify predictors for success in physiology. Methods. A quantitative study, using Matric and available NBT results, was conducted among the MB ChB II group (N=228) of 2011. Two target groups were identified: highly successful students in physiology (n=37) and those who failed (n=46). Statistical analysis of the results was performed on SAS 9.2, Microsoft Windows (SAS Institute Inc., USA) (p-values ≤0.05 are significant) using the t-test, Fisher’s exact test and the simple linear regression test. Results. These indicated that a good Matric symbol (≥5) in English and life science and a good performance in the quantitative literacy domain of the NBT were statistically significant predictors for success in physiology. Conclusion. This preliminary study indicates the need for our institution to rethink the effectiveness of the selection criteria, redesign the selection process of students for the MB ChB course, and consider making use of the NBT.